2016
DOI: 10.1074/jbc.m116.762476
|View full text |Cite
|
Sign up to set email alerts
|

Direct Involvement of the Master Nitrogen Metabolism Regulator GlnR in Antibiotic Biosynthesis in Streptomyces

Abstract: Edited by Joel GottesfeldGlnR, an OmpR-like orphan two-component system response regulator, is a master regulator of nitrogen metabolism in the genus Streptomyces. In this work, evidence that GlnR is also directly involved in the regulation of antibiotic biosynthesis is provided. In the model strain Streptomyces coelicolor M145, an in-frame deletion of glnR resulted in markedly increased actinorhodin (ACT) production but reduced undecylprodigiosin (RED) biosynthesis when exposed to R2YE culture medium. Transcr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
32
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 32 publications
10
32
0
Order By: Relevance
“…In actinomycetes, GlnR was typically viewed as a global nitrogen metabolism regulator before, governing many nitrogen metabolism related processes (Fink et al, 2002;Tiffert et al, 2008;Wang and Zhao, 2009;Wang et al, 2012Wang et al, , 2013Wang et al, , 2014. Recently, several studies have reported that the GlnR homologs in Streptomyces regulate the biosynthesis of some antibiotics, e.g., actinorhodin, avermectin and validamycin (Qu et al, 2015;He et al, 2016). Here our study also shows that the GlnR in A. mediterranei directly controls the rifamycin biosynthesis.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…In actinomycetes, GlnR was typically viewed as a global nitrogen metabolism regulator before, governing many nitrogen metabolism related processes (Fink et al, 2002;Tiffert et al, 2008;Wang and Zhao, 2009;Wang et al, 2012Wang et al, , 2013Wang et al, , 2014. Recently, several studies have reported that the GlnR homologs in Streptomyces regulate the biosynthesis of some antibiotics, e.g., actinorhodin, avermectin and validamycin (Qu et al, 2015;He et al, 2016). Here our study also shows that the GlnR in A. mediterranei directly controls the rifamycin biosynthesis.…”
Section: Discussionsupporting
confidence: 70%
“…The phenotypic analyses (Figure 1 and Supplementary Figure S2) showed that, unlike the previous work in Streptomyces (He et al, 2016), the cellular growth under our cultivation conditions was not impaired by glnR deletion at all, which ruled out the impact of the growth factor on gene transcription and on antibiotic production, thus making our conclusions from this study (especially the Figures 1, 2 and Supplementary Figures S2, S3) more reliable. The Supplementary Figure S2B showed that glnR had a significantly lower yield of rifamycin comparing with the wild type U32 when grown in liquid Bennet medium without nitrate, whereas in our previous work, the rifamycin yield of glnR was a little bit higher than that of U32 when grown on Bennet agar plates without nitrate supplementation (Yu et al, 2007).…”
Section: Discussionsupporting
confidence: 45%
See 1 more Smart Citation
“…Indeed, the same plasmid has been used by other research groups to edit streptomycete genomes. [34][35][36][37][38] For instance, the same authors later used this toolkit on S. pristinaespiralis to study the regulation of the biosynthesis of the antibiotic pristinamycin I through generation of point-mutations, 34 as well as to increase its production titres through deletion of the cluster-specic transcriptional repressors. 35 In two other instances pKCcas9dO has been used to edit the genome of S. coelicolor: (i) to study the regulation mechanism of the two-component system AfsQ1/Q2 in coelimycin P2 biosynthesis, 36 and (ii) to conrm the involvement of the global transcriptional regulator GlnR in antibiotic biosynthesis regulation.…”
Section: Pkccas9do Plasmid From Hu Lu and Colleagues 11mentioning
confidence: 99%
“…This activation is in many instances indirectly mediated by the master response regulator PhoP via signal transduction cascades, which ultimately activate pathway-specific regulators (Rodríguez-García et al, 2007). Similarly, GlnR, the master response regulator for nitrogen metabolism in actinomycetes, which also plays an important role in carbon uptake and metabolism in these organisms (Liao et al, 2015), has been recently found to directly activate pathway-specific regulators of specialised metabolites in several actinomycete genera (Yao et al, 2014;He et al, 2016).…”
Section: Physiological Regulation -Integrating Starvation Signals In mentioning
confidence: 99%